Feminist research in agriculture: moving beyond gender-transformative approaches - Cole, S.M.; Rajaratnam, S.; Liani, M.; Joshi, D.; Basnet, S.; Bisht, M.; Shijagurumayum, M.S.; Jain, M.; Kumar, P.; Fischer, K.; Puozaa, D.K.; Reyes, A.; et al. (Springer, 2024)
Feminist research approaches in agriculture are considerably underutilized. In this chapter, we suggest a few key reasons to help explain their lack of use in agriculture. We also provide background on what constitutes feminist research in agriculture through a review of the literature. Using a case study approach, we highlight the important and unique characteristics that define feminist research approaches in agriculture. The case studies provide examples of how researchers working in agriculture can gradually adopt key feminist research principles. We argue that to transform agrifood systems to be more inclusive, equitable, and sustainable, feminist approaches must be used in all research in agriculture. The chapter concludes by discussing what is needed to increase the use of feminist research approaches in agriculture, recognizing that resistance to change is inevitable and requires commitment at the top to spearhead efforts to institutionalize feminist approaches within agricultural research organizations.